All-sky-imaging capabilities for ionospheric space weather research using geomagnetic conjugate point observing sites. Issue 7 (1st April 2018) - Martinis, C.; Baumgardner, J.; Wroten, J.; Mendillo, M.
Abstract: Optical signatures of ionospheric disturbances exist at all latitudes on Earth—the most well known case being visible aurora at high latitudes. Sub-visual emissions occur equatorward of the auroral zones that also indicate periods and locations of severe Space Weather effects. These fall into three magnetic latitude domains in each hemisphere: (1) sub-auroral latitudes ∼40–60°, (2) mid-latitudes (20–40°) and (3) equatorial-to-low latitudes (0–20°). Boston University has established a network of all-sky-imagers (ASIs) with sites at opposite ends of the same geomagnetic field lines in each hemisphere—called geomagnetic conjugate points . Our ASIs are autonomous instruments that operate in mini-observatories situated at four conjugate pairs in North and South America, plus one pair linking Europe and South Africa. In this paper, we describe instrument design, data-taking protocols, data transfer and archiving issues, image processing, science objectives and early results for each latitude domain. This unique capability addresses how a single source of disturbance is transformed into similar or different effects based on the unique "receptor" conditions (seasonal effects) found in each hemisphere. Applying optical conjugate point observations to Space Weather problems offers a new diagnostic approach for understanding the global system response functions operating in the Earth's upper atmosphere.